Analisis Pemanfaatan Literasi Digital Mahasiswa Program Studi Pendidikan Ekonomi FKIP Universitas Muhammadiyah Bengkulu - Rossa Ayuni; Rahmi Gustina (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to determine the use of digital literacy for Students of the Economic Educaation Study Program FKIP Muhammadiyah University Bengkulu. This research uses Descriptive. The data sources in this study are Primary data and Secondary data. This research data collection technique uses Observation, Interviews, and Documentation. There are three (3) data analysis techniques, namely Data Reduction, Display Data, and Conclusion Drawing/Verification Data. The results of research on the use of Digital Literacy for Students of the Economic Education Study Program at the University of Muhammadiyah Bengkulu using three (3) indicators, namely the Intensity of application and use of digital literacy in learning activities, all Students of the Economic Education Study Program Class of 2022 are very intense in utilizing digital literacy, in the teaching and learning process Students always use digital literacy to find learning resources, doing assignments both on campus and at home, in terms of the number and veriety of reading materials and digital-based teaching aids, students are greatly helped by the variety of readings that can be used according to their needs in learning, variations of student reading materials using blogspot, journals, web and google books, which are used according to the needs in learning, the frequency of borrowing digital-themed books, the existence of digital-themed books helps students in the process of finding learning resources, doing assignments and getting various books quickly.